"More than Meets the Eye": When the Neonatal Course May Impact Several Years Out. Issue 1 (February 2017) - Dopwell, Fadiyla; Maypole, John; Sinha, Bharati; Currier, Heidi; DeBassio, William; Augustyn, Marilyn
Abstract : CASE: Nadia is a 7-year-old girl who you have followed since her discharge from the Neonatal Intensive Care Unit (NICU). Her parents are here today for an urgent visit with behavioral concerns, such as inattention, hyperactivity, and aggression. Nadia is a former 40-weeker born through vacuum-assisted vaginal delivery at 9 pounds 7 ounces. Her delivery was complicated with shoulder dystocia, which resulted in resuscitation. Her Apgar scores were 1, 3, and 4 at 1, 5, and 10 minutes, respectively. After intubation and stabilization on mechanical ventilation, Nadia was transferred to the NICU. Her neonatal course included systemic hypothermia using "cool cap" for hypoxic-ischemic encephalopathy (HIE) for a duration of 72 hours. She was extubated on day of life 3. She had an occupational therapy consultation for poor suck/feeding, and it quickly improved. She was discharged on day of life 14. On discharge, Nadia was referred to early intervention (EI) and the NICU follow-up clinic. Nadia was followed by EI until 12 months of age and in the NICU follow-up clinic until 18 months of age, as there were no concerns meeting her developmental milestones or her neuromotor development. At this urgent visit, Nadia's parents report that she attended a family child care from 1.5 to 3 years of age, Head Start from 3 to 5 years of age and the local public school from 5 years to present. Since starting child care, Nadia's teachers have reported that she requires a lot of redirection and refocusing, fidgets a lot in class, and can be aggressive toward her peers when unprovoked. Since her parents had not seen these behaviors at home, they thought it was a phase that she would grow out of. However, as they began to work with her to complete school assignments, they noticed that it was very difficult for Nadia to sit still and focus on work. They also struggled in the mornings to get her ready and off to school. The parents bring in Conners scales completed by themselves and her lead teacher, and with these and our clinical observations, we diagnose her with attention-deficit/hyperactivity disorder (ADHD), combined type. We discuss risk factors and ADHD management with her parents. During our discussion, Nadia's father, who has done some reading on ADHD, remembers reading an article about HIE and NICU stay being risk factors for ADHD. He wonders if this affects the choice of management of her ADHD symptoms. How would you address his query?